BETWEEN LEGAL REFORM AND JUDICIAL PRACTICE: THE PARADOX OF MARRIAGE DISPENSATION AND CHILD RIGHTS PROTECTION IN INDONESIAN RELIGIOUS COURTS - Abdul Halim (JURNAL HAKAM, 2025)
Indonesia’s amendment of Law No. 16 of 2019, which raised the minimum marriage age for women from 16 to 19 years, represents a landmark legal reform aimed at eradicating child marriage and upholding the best interests of the child. However, the persistence of marriage dispensation petitions (dispensasi kawin) filed before Indonesian Religious Courts (Pengadilan Agama) reveals a profound paradox: legislative reform has not translated into proportional judicial protection of child rights. This article critically examines the tension between the spirit of legal reform and entrenched judicial practice in marriage dispensation proceedings. Drawing on a normative-empirical legal research approach, this study analyzes judicial decisions, court statistics, and doctrinal frameworks through the lens of child rights theory and progressive law theory. Findings reveal that despite reformative legislative intent, Religious Courts continue to grant the overwhelming majority of dispensation petitions, frequently citing pregnancy, social pressure, and economic hardship as justifying grounds without adequately weighing the long-term developmental rights of the child. The article argues that this paradox is produced by a confluence of factors including interpretive conservatism among judges, structural gaps in procedural law, insufficient multi-sectoral child protection infrastructure, and the unresolved tension between Islamic family law norms and international child rights standards. The study concludes by proposing a rights-based judicial methodology, enhanced judicial training, and interdisciplinary court-annexed support mechanisms as pathways toward substantive convergence between legal reform and judicial practice.